Measuring Public Opinions on Renewable Energy and Climate Change Using Structural Equations Modeling - Ionut Nica; Simona-Vasilica Oprea; Adela Bara (IEEE Access)
Public attitudes towards energy sources and climate change are increasingly complex. This paper explores Americans’ perceptions of energy sources including renewables, Electric Vehicles (EVs), government policies and climate change. A survey conducted by the Pew Research Center (PRC), comprising over 10,000 responses to 52 questions on energy sources and climate change, is analyzed. In this paper, we propose a data analysis framework that consists of Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), cluster analysis and Principal Component Analysis (PCA) to segment respondents and identify key variables. Furthermore, the Structural Equation Model (SEM) is created to examine relationships between latent and observed variables, using maximum likelihood estimation. The results validated the identified factors, with high loading on key variables indicating strong contributions to attitudes towards energy and climate policies.